Investigation of the proinflammatory activity of bronchoalveolar lavage fluid in lung cancer and inflammatory diseases of respiratory organs - O. P. Makarova; L. N. Shishkina; A. P. Ogirenko (Туберкулез и болезни лёгких, 2014)
The proinflammatory activity of bronchoalveolar lavage fluid (BALF) was investigated using the biological test system (donor blood) in 71 patients with lung cancer and inflammatory disease of respiratory organs (lung abscess, infiltrative tuberculosis, tuberculoma, fibrocavernous tuberculosis). The supernatant of BALF was purified by filtration through millipores and added to blood, and a nitroblue tetrazolium recovery test (HBT) was carried out. Hank’s balanced salt solution was used in the control. The proinflammatory effect of BALF was defined as a diformazan-positive neutrophil count ratio in the experimental and control samples (stimulation index). The inflammatory process developing in lung cancer was active, as suggested by the accumulation of neutrophils in the lung and by the high proinflammatory activity of BALF, which were comparable with the similar indicators in lung abscess and fibrocavernous tuberculosis.